ФІНАНСОВА ПІДТРИМКА ЕКОНОМІКИ УКРАЇНИ В УМОВАХ ВІЙНИ - Kovpaka, Anastasiya (Zhytomyr Ivan Franko State University, 2022)
The scientific article is devoted to the analysis of the priority directions of state financing in the conditions of war, coordination of fiscal and monetary policy instruments to meet the defense needs of Ukraine and determination of the causes of Ukraine's public debt. In the course of the study, the main sources of filling the state budget were analyzed. It is established that tax and non-tax revenues, income from capital transactions, transfers formed the basis of state revenues in the pre-war period.  It is revealed that in the conditions of war the state is acutely dependent on external financing and domestic borrowing.  International loans, grants and proceeds from the sale of bonds (including military bonds) become effective means of covering the state budget. The article contains information on the implementation of this year's state budget and analysis of the structure of financial revenues to the budget of Ukraine from external sources for 2022.  The article summarizes the priority areas of public spending: army, social security, education, medicine and post-war reconstruction.  Among them, defense expenditures occupy the largest part. The structure of social payments is investigated, among which the following key areas of financing are highlighted: pension fund, assistance to families with children and internally displaced persons, "ePidtrymka", benefits and subsidies. It is proved that the solution of the problem of financial support of the Ukrainian economy in the conditions of war requires a balanced combination of monetary and fiscal policy instruments. Today, the budget deficit is covered mainly by international financing and by selling government securities. The deficit of expenditures should be financed by non-monetary means, as excessive dependence on money emission intensifies  inflationary processes.